MENINGKATKAN KETERAMPILAN MENULIS PUISI MELALUI MEDIA TULISAN BERGAMBAR (MEME) DI INSTAGRAM PADA PESERTA DIDIK KELAS VIII G SMPN 24 SURABAYA - Prily Yulia Utomo Putri; Tri Indrayanti (Buana Bastra, 2020)
This research is a research follow class by using the secound cycle that there is the first cycle and cycle II. On the cycle I and cycle II each cycle there four stage of the (1) planning, (2) implementation of action, (3) observations, and (4) reflection. Each cycle has two meetings in one week, namely the first meeting and the second meeting with the allocation 2 x 40 minutes of each meeting. Subject in research is learners class VIII G SMPN 24 Surabaya totaling 37 learners contained 16 learners men and 21 learners woman. This school is located in Jl. Kebraon Indah Permai Blok K/23 A Surabaya. Data collection techniques to use the observation and test, data analysis technique using the percentage of. Based on the results of data analysis, it can be concluded that using pictorial writing media on the meme on Instagram can improve the writing skills of class students VIII G SMPN 24 Surabaya. This can be seen from (1) population activity in the cycle I 84,61% on the cycle II 100%, (2) activity learners in cycle I 83,44% on the cycle II 90,20%, (3) the test results writing skills poerty in cycle I 56,73% one the cycle of II increased 83,70%.